Ultrasound promoted copper-, ligand- and amine-free synthesis of benzo[b]furans/nitro benzo[b]furans via Sonogashira coupling-5-endo-dig-cyclization - Palimkar, Sanjay S.; More, Vijaykumar S.; Srinivasan, Kumar V. (Ultrasonics Sonochemistry, 2008)
This method describes the results of the optimized conditions for the one-pot synthesis of benzo[b]furans/nitro benzo[b]furans via Sonogashira coupling-5-endo-dig-cyclization under ultrasonic irradiation at ambient temperature in the absence of copper, ligand and amine. The protocol tolerates wide range of functional groups present in both the coupling components, especially base labile nitro group was not affected under these mild conditions giving excellent yields of the nitro benzo[b]furans. The formation of Pd(0) nanoparticles as the active species has been shown by TEM analysis and the unique role of ultrasound in promoting the total sonochemical protocol has been substantiated by way of control experiments. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: 1-alkynes; benzo[b]furans; Sonogashira coupling-5-endo-dig-cyclization